Sustainability Reporting from the Perspective of IFRS S1 and IFRS S2: A Bibliometric Study - Loso Judijanto; Bintang Cahya; Rully Fildansyah (West Science Social and Humanities Studies, 2026)
Since the International Sustainability Standards Board (ISSB) issued IFRS S1 and IFRS S2 in June 2023, sustainability reporting has entered a phase of accelerated standardization. This study conducts a bibliometric analysis to investigate the intellectual structure, publication trends, influential authors, and collaboration patterns of research examining sustainability reporting from the perspective of IFRS S1 and IFRS S2. Data were retrieved from Scopus using keyword combinations built around "IFRS S1", "IFRS S2", "sustainability reporting", "ISSB", and "sustainability disclosure", and analyzed with VOSviewer to construct keyword co-occurrence, overlay, density, co-authorship, institutional, country-collaboration, and citation networks. Results show that sustainability reporting functions as the central bridging term linking three clusters: an ESG-accounting and disclosure cluster, a sustainable-development and environmental-legacy cluster, and an IFRS S1–S2/ESG/climate-disclosure cluster, connected through a smaller regulatory-accounting cluster. The overlay analysis indicates that IFRS S1, IFRS S2, and core accounting terms are established anchors, while corporate governance, ESG reporting, and sustainability accounting are emerging themes. Co-authorship and institutional mapping reveal a field still dominated by small, tightly-knit, geographically concentrated teams, most visibly a single fully-connected Ghanaian cluster investigating IFRS S1/S2 implementation readiness. Country mapping identifies the United Kingdom as the principal collaboration hub, linked to South Africa, Italy, Egypt, and Indonesia. Citation analysis identifies ESG reporting and metrics scholarship and systematic reviews of sustainability reporting as the most influential works, alongside emerging implementation-focused contributions. This study contributes a structured map of this rapidly forming research landscape and identifies priority directions for future scholarship.